Specific proteome changes in platelets from individuals with GATA1-, GFI1B- and RUNX1-linked bleeding disorders - van Bergen, Maaike G J M; Marneth, Anna E; Hoogendijk, Arie J; van Alphen, Floris; van den Akker, Emile; Laros-van Gorkom, Britta; Hoeks, Marlijn; Simons, Annet; de Munnik, Sonja; Janssen, Jeroen Jwm; Martens, Joost; Jansen, Joop H; et al. (Blood, 2021)
Mutations in the transcription factors GATA1, GFI1B and RUNX1 (GATA Binding Factor 1, Growth Factor Independence 1B, Runt-related transcription factor 1) cause familial platelet and bleeding disorders. Mutant platelets exhibit common abnormalities including an α-granule reduction resulting in a grayish appearance in blood smears. This suggests that similar pathways are deregulated by different transcription factor mutations. To identify common factors, full platelet proteomes from 11 individuals with either mutant GATA1R216Q, GFI1BQ287*,RUNX1TD2-6, or RUNX1Q154Rfs, and 28 healthy controls were examined by label free quantitative mass spectrometry. In total, 2875 platelet proteins were reliably quantified. Clustering analysis of over 300 differentially expressed proteins revealed profound differences between cases and controls. Among cases, 44 of 143 significantly downregulated proteins were assigned to platelet function, hemostasis and granule biology, in line with platelet dysfunction and bleedings. Remarkably, none of these proteins were significantly diminished in all affected cases. Similarly, no proteins were commonly overrepresented in all affected cases compared to controls. These data indicate that the here studied transcription factor mutations alter platelet proteomes in distinct largely non-overlapping manners. This work provides the quantitative landscape of proteins that affect platelet function when deregulated by mutated transcription factors in inherited bleeding disorders.